Fruit based nutri-bars for rural and urban nutrition security - Singh, Abha; Gupta, Alok Kumar; Singh, Akath (Indian Horticulture, 2026)
The ICAR-Central Institute for Subtropical Horticulture (CISH) has developed advanced technologies for raw mango, ripe mango, guava nutri bites, and jamun fruit bars aimed at improving nutritional content and facilitating fruit utilization. These products utilize the abundant antioxidant, vitamin, and mineral composition of these fruits, providing nutritious and convenient snack options. This technology enhances shelf life, minimizes postharvest losses, and facilitates value addition for agricultural producers. It additionally fosters entrepreneurship and sustainable agriculture via scalable processing techniques. These advancements improve food security and deliver nutritious, commercially viable products for consumers.